Male and Female Teachers’ Opinion towards Digital Literacy Training - Zaiyana Putri; Marisa Yoestara; Munawir Munawir (International Conference on Multidisciplinary Research, 2022)
This study aims to examine differences between male and female teachers’ perception of the digital literacy training. The design of the study was descriptive quantitative study, in which the researchers described differences in both male and female teachers’ perception in the digital literacy training conducted in Pidie Jaya. 16 senior high school teachers in SMA Negeri 1 Bandar Baru became the participants of the study. There were 6 male teachers and 10 female teachers. The researchers used the questionnaire that was developed to find out perception in terms of 5 aspects; speakers, participants, materials, atmospheres, and facilities. The data were then analyzed through some steps including grouping the data based on gender and finding the average percentage of each aspect based on gender. The results show that both male and female agreed that the digital literacy training conducted was very effective. A small number of female teachers thought that materials, atmospheres, participants, and facilities were not very effective. For male teachers, only materials and speakers that were claimed to be not very effective, 3% and 4% respectively. Keywords: Male and Female Teachers, Perception, Digital Literacy Training